The Inside of a School - or the First Meeting - after the - Holidays;.!!! - Cawse? (Fores, S. W., 1800)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Great Britain -- Politics and government -- 1800-1837